Effect of porosity of goethite on the sorption of six heavy metal ions. (25th September 2013) - Brümmer, G. W.; Barrow, N. J.; Fischer, L.
Summary Seven different samples of goethite with differing crystallinity were prepared and the rate of reaction of six metal ions was measured for up to 4 weeks. The ions used were: Cu2+, Pb2+, Cd2+, Mn2+, Ni2+ and Cr3+. For Cu, decreasing goethite crystallinity, and therefore increasing porosity, increased the rate of reaction. In contrast, for Pb there was no effect. Hydrothermal treatment, which was used to induce 'healing' in one of the goethites, did not prevent the continuing reaction. It decreased the rate of reaction for Cu, Mn and Cd, but had no effect on Ni and Cr. This suggests that the main route for Ni and Cr is not via pores, but by lattice diffusion. The presence of silicate in the goethite decreased the reaction of Mn and Cd. We suggest that silicate decreased the spaces between goethite domains and that these spaces are the pathways largely used by these two ions. These observations show that metallic cations differ amongst themselves, and differ from anions such as phosphate, in the pathways they follow when they penetrate materials such as goethite subsequent to an initial adsorption reaction.